BISPHOSPHONATE IN DENTİSTRY - Gunduz, Alpaslan (Brazilian Journal of Implantology and Health Sciences, 2024)
Abstract Bisphosphonates are widely used in a variety of conditions, particularly in postmenopausal women to prevent age-related osteoporosis and associated fractures. They are also used to treat malignant hypercalcemia, Paget's disease, and to prevent bone metastases from cancers such as lung, prostate, and colon cancer. However, a significant side effect of bisphosphonate therapy is the potential for bone tissue necrosis. Bisphosphonate-induced osteonecrosis of the jaw (BIONJ) is a particularly common complication in patients receiving bisphosphonate therapy. This condition primarily affects the maxilla and mandible, areas that undergo bone remodeling at a higher rate than other sites in the skeleton. The clinical presentation of BIONJ can be highly variable, ranging from localized, non-healing bone lesions to extensive areas of exposed necrotic bone. This variability in presentation presents significant challenges for diagnosis and management in the dental office. Given the prevalence of bisphosphonate use and the associated risks, dentists must exercise caution when treating patients on these medications. For patients diagnosed with BIONJ, it is essential that dental treatment plans are developed in close collaboration with relevant medical specialists. Ideally, comprehensive dental treatment should be completed prior to initiation of bisphosphonate therapy to minimize the risk of complications. The purpose of this study is to review and present current treatment modalities for patients on bisphosphonate therapy, focusing on both the systemic and local effects of these drugs. By synthesizing the most recent literature, this study aims to provide evidence-based guidelines for dental practitioners managing patients who are either currently taking bisphosphonates or have a history of bisphosphonate use.